1985
DOI: 10.1002/em.2860070312
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nitrilotriacetic acid with heavy metals in the induction of sister chromatid exchanges in cultured mammalian cells

Abstract: The ability of nitrilotriacetic acid trisodium salt (NTA) to induce sister chromatid exchanges (SCE) and to influence the induction of SCE by heavy metal compounds was evaluated with mammalian cell cultures. In accordance with the generally negative results obtained by other investigators on the mutagenic effects of NTA, no increase of SCE frequency was observed in Chinese hamster cells (CHO line) or in primary cultures of mouse (BALB/c and BALB/Mo strains) lymphocytes, after treatment with NTA at subtoxic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…47 We previously demonstrated that the interaction of NTA with the metal cations present in insoluble Cr(VI) compounds (Pb, Ba, Zn, Sr and Ca chromâtes) results in the release of soluble chromate anion and induces a proportional increase of gene mutations in S. typhimurium and SCE in cultured mammalian cells. 22 -23 Present results, as well as those of a previous investigation, 24 clearly show that, whereas NTA does not significantly modify the genetic activity of soluble salts of Cd(II), Cr(VI), Hg(II), Ni(II) and Pb(II), the ability of insoluble metal compounds of Cd(II), Cr(VI), Hg(I), Ni(II) and Pb(II) to induce SCE in cultured hamster cells, as well as micronuclei and chromosomal aberrations in human lymphocytes, is significantly increased in the presence of NTA.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…47 We previously demonstrated that the interaction of NTA with the metal cations present in insoluble Cr(VI) compounds (Pb, Ba, Zn, Sr and Ca chromâtes) results in the release of soluble chromate anion and induces a proportional increase of gene mutations in S. typhimurium and SCE in cultured mammalian cells. 22 -23 Present results, as well as those of a previous investigation, 24 clearly show that, whereas NTA does not significantly modify the genetic activity of soluble salts of Cd(II), Cr(VI), Hg(II), Ni(II) and Pb(II), the ability of insoluble metal compounds of Cd(II), Cr(VI), Hg(I), Ni(II) and Pb(II) to induce SCE in cultured hamster cells, as well as micronuclei and chromosomal aberrations in human lymphocytes, is significantly increased in the presence of NTA.…”
Section: Discussionsupporting
confidence: 68%
“…23 NTA also increases the ability of insoluble compounds of Cd(II), Hg(I), Ni(II) and Pb(II) to induce SCE in cultured hamster CHROMOSOMAL EFFECTS OF NTA-METALS 185 cells while apparently it does not affect the induction of SCE by soluble metal compounds. 24 In our previous investigation 24 only a few concentrations of insoluble metals were tested, therefore a clear dose-effect relationship could not be obtained. Moreover, an interaction of NTA with the soluble metal compounds could not be excluded as, even in the absence of NTA, the metal concentrations tested already increased the SCE frequency to its upper limit, above which toxic effects were produced.…”
Section: ' 15~17mentioning
confidence: 97%
See 2 more Smart Citations
“…cerevisiae [Loprieno et al, 19851, DNA damage and repair in E. coli [Celotti et al, 1987b], DNA repair synthesis [Williams et al, 19821 and sister chromatid exchanges [Ved Brat and Williams 1982;Montaldi et al, 1985, 19871 in cultured mammalian cells, and sister chromatid exchanges in developing eggs of the marine mussel Mytilus galloprovincialis [Brunetti et al, 19861;4) in vitro transformation of BHK21k13 hamster cells [Lanfranchi et al, 19881. Some positive results also were obtained with NTA in short-term genotoxicity tests. The relevance of these, however, is lowered by some discrepancies and criticisms: 1) Gene mutations in human cells cultured in vitro were positive for the induction of resistance to dyphteria toxin [Grilli and Capucci, 19851, but this is not a widely used test, and the results are not confirmed using the more validated tests based on resistance to base analogues [NTP, 1983;Celotti et al, 1987al. 2) Chromosomal aberrations and/or micronuclei were observed after very long treatments with extremely high NTA concentrations in cultured cells of V. faba [Kihlman and Sturelid, 1970;De Marco et al, 19861, A. cepa [De Marco et al, 19861, rat kangaroo [Kihlman and Sturelid, 19701, and human lymphocytes [Bora, 19751; however, these results were not confirmed by more conventional treatment conditions [Montaldi et al, 1987;19881. 3) Binding to mammalian cell DNA in vitro [Colacci, 19851 and DNA damage in E. coli [Venier et al, 19871 were observed with systems not usually included among those employed to detect this kind of genetic effect, such as DNA repair synthesis and sister chromatid exchange assays, which gave absolutely negative results for NTA [Williams et al, 1982;Ved Brat and Williams, 1982;Montaldi et al, 1985;19871. 4) The efficiency of NTA in inducing mammalian cell transformation in cultured BALBk-3t3 mouse cells [Sivak, 19831 as well as in rat embryo cells infected with leukemia virus [Traul et al, 19811 is very low and borderline significant; thus, the results were scored as questionable [NTP, 19831. Therefore, it must be concluded that the weight of the evidence indicates that NTA is unable to induce direct genetic effects.…”
Section: Discussionmentioning
confidence: 99%